Hell freezes over: creating conditions for success in Arctic ground combat. - Nolan, Ross (Fort Leavenworth, KS : US Army Command and General Staff College, 2022)
As climate change has increased the accessibility of the Arctic for economic activity and as NATO competition with the Russian Federation has intensified, the Arctic is rapidly emerging as an increasingly important region of strategic importance. The U.S. is an Arctic nation by way of Alaska but lacks ground combat organizations that are specifically built to dominate a near-peer enemy in what is one of the most harsh environments in the world. This thesis seeks to identify force modernization priorities for the U.S. Army by conducting a historical case study analysis to identify the most important factors that have resulted in success during combat in the Arctic and extreme cold weather regions in the past. This study uses factors from the case study analysis to compare the U.S. and Russian Arctic ground combat forces and recommends force updates to close identified capability gaps.